Model Komunikasi Kyai Dengan Santri di Pesantren - Mansur Hidayat (Asosiasi Pendidikan Tinggi Ilmu Komunikasi (ASPIKOM), 2016)
The existence of Islamic boarding school (pesantren) can’t be separated from the figure of a clerics (kyai) and the communication between clerics and students (santri). Using qualitative research approach, this study aims to to prepare, understand and analyze communication models between clerics and students in Pesantren Raudhatul Qur’an An-Nasimiyyah. Communication Model between clerics and students in Islamic boarding school is influenced by the concept of Morals, status and charisma of clerics. Moral education is a way to establish communication that facilitates management of transfer of knowledge to students. Status and charisma of clerics are enhancer factor communicator legitimacy in the context of Islamic boarding school. The research concludes that the construction of communications models of clerics and students was formed by high-intensity interactions between clerics and students.